Proposta metodológica para a pré-seleção de sistemas de tratamento de esgoto no âmbito de bacias hidrográficas - Fantin, Lucas Luiz Dall'Orto (2016)
Disposal of sewage into water bodies is one of the major environmental degradation problems. Implementation of sewage treatment plants represents the most common alternative for reduction and control of the resulting pollution.The selection of sewage treatment plants within watersheds is a complex process when there are multiple outflows presenting different loads and watercourses presenting different assimilation capabilities.In this context, the present study aims to establish a methodology for pre-selection of wastewater treatment alternatives within watersheds. The methodology involves the combined use of water quality model, optimization technique and a set of technical and economic criteria associated with different wastewater treatment systems. The combination of water quality model and Genetic Algorithm, ina Matlab software computing environment, allowed the minimization of the sum of efficiencies of the considered sewage treatment plants. Two different optimization objectives were adopted. The first objective searched the minimization of thesum of treatment efficiencies within the watershed while the other alsosought to establish equity between efficiencies fordifferent systems.To evaluate the proposed methodology there were considered different effluentdisposal scenarios in the Pardo river watershed, a major tributary of the Itapemirim river, watercourse located in the southern portion of Espírito Santo state, Brazil. The results indicated that the optimization model, that aimed to minimize wastewater treatment efficiencies within the watershed, considering self-purification capacities of watercourses, selected treatment systems ranging from the combination of UASB and polishing lagoons systems to slow infiltration, treatment alternatives that presented the lowest net cost estimates. The incorporation of equity between treatment systems increased the total present net cost associated with the treatment of wastewater within the watershed.